PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA KANTOR IMIGRASI KELAS I TPI MALANG UNIT KERJA KEIMIGRASIAN DI PROBOLINGGO - Elfany, Faiz Ibadillah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This research aims to find out the description of leadership effect and motivation on employee performance thorough job satisfaction at the TPI Malang Class I Immigration Office, Immigration Work Unit in Probolinggo. The research was conducted at the TPI Malang Class I Immigration Office, Immigration Work Unit in Probolinggo and the sample in this study were all 32 employees using a saturated sampling method, namely using the entire population as the sample. Data collection was carried out by distributing questionnaires to employees. Data were analyzed using quantitative descriptive analysis with partial least squares. Based on the results of the analysis, this research sample found that Leadership has no influence on Employee Job Satisfaction, Leadership has no influence on Performance, Motivation has an influence on Job Satisfaction, Motivation has an influence on employee Performance, Job satisfaction has an influence on employee performance, Leadership has no influence on employee performance through employee job satisfaction, Motivation has no influence on Employee Performance through Employee Job Satisfaction.